Cultures in conflict - the Arab Israeli conflict - Goldscheider, Calvin (Greenwood Press cultures in conflict series, 2002)
The conflict in cultures between the Arabs and the Israelis is brought to life in the first person accounts, letters, memoirs, and stories of ordinary people caught in the strife.